Effects oF Chitosan as Bio-Mordant on Cotton Fabric Dyeing with Various Natural Dyes - Rachma Tia Evitasari; Zahrul Mufrodi; Selva Mazareta; Jiran Nirmalasari (Balai Besar Standardisasi dan Pelayanan Jasa Industri Kerajinan dan Batik, 2023)
Natural dyes are alternatives to synthetic dyes as batik dyes. However, color results produced by natural dyes were not as good as synthetic dyes, hence mordant compounds were required. As a substitute for metal mordant, it was essential to have another alternative mordant, such as chitosan. This research was intended to analyze the color produced by various sources of natural dyes, betel nut; spurred mangrove (tingi) bark; baheda (jolawe) peel; mangrove bark; mahogany bark; and copperpod (jambal) bark, quantitatively by testing the value of color differences (ΔE) on variations of the chitosan concentration and fabric dyeing. In conclusion, the use of chitosan could enhance the absorption of dye into the fabric. In a chitosan concentration of 10 g/L, betel nut reached an ΔE value of 15.40; spurred mangrove 16.26; baheda peel 18.97; mangrove 10.87; mahogany 14.01; and copperpod 19.33. Furthermore, the test of fastness to sunlight with greyscale showed the value in range of 4-5 (good).